Integration of Physical and Mental Health through the Adolescent Posyandu Program in Wedung District, Demak Regency, Central Java - Cahyo Wulandari; M. Zahrandika Putra Raihan; Salma Salsabila Firdausa; Siti Aisyah (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The adolescent phase is a transitional period from childhood to adulthood, marked by rapid physical growth, maturation of sexual function, and cognitive-mental development. These changes are inevitably accompanied by their related issues; adolescents may struggle with physical changes, overwhelmed by emotional changes, and face psychological pressures they have never experienced before. Therefore, during the KKN-PPM UGM 2024, unit JT-013 conducted several programs aimed at fostering the physical and mental health of adolescents in Wedung District, Demak Regency. These activities include Posyandu Remaja and counselling on Recognizing and Regulating Emotions. This article aims to provide an overview of the program's implementation and present the findings obtained. Data collection was carried out through health examinations, quantitative instruments in the form of questionnaires, and interviews with participants and partners involved in the program. Health examinations provided a general overview of adolescents' health status, especially concerning non-communicable disease. Anthropometric assessments revealed that 60,8% of participants in Wedung Village had low body mass index (BMI) issues. Blood pressure measurements generally showed good results; however, 43,4% of participants in Wedung Village and 29,7% of participants in Tedunan Village had their blood pressures elevated above normal. Haemoglobin tests indicated that 78,9% of participants in Wedung Village experienced anemia. Mental health screening by the KKN Team using DASS-21 showed issues in the categories of depression, anxiety, and stress among adolescents in Wedung and Tedunan. The counselling on Recognizing and Regulating Emotions showed a significance value of p < 0.05 on 2 out of 4 measured indicators. This indicates a significant change in those two indicators. The results of these activities highlight the importance of paying greater attention to the physical and mental health of adolescents.